Lithium bioaccumulation capacity by basidiomycetes - a brief review (Research, Society and Development, 2020)
Lithium salts are used in mood disorders, since this chemical element acts on the central nervous system. To increase the bioavailability of this metal, strategies are studied, such as bioaccumulation in basidiomycetes. Thus, the goal of project was to carry out a bibliographic review on the capacity of in vitro lithium bioaccumulation by basidiomycetes. Scientific articles on biocumulation, lithium and basidiomycetes published in the 1980s to 2020s were researched. An alternative for the treatment of bipolar mood disorder is lithium carbonate, but its therapeutic range is narrow, which can lead to drug intoxication. In vitro lithium bioaccumulation in basidiomycetes can help to reduce side effects and improve the bioavailability of lithium. Studies on lithium bioaccumulation in basidiomycetes are scarce, and most of them use LiCl as a source of lithium, probably due to its high solubility. The mycelial culture of fungi in liquid medium has been the best option for the production of lithium enriched biomass. Among the analyzed studies, Pleurotus ostreatus is the most studied species in lithium bioaccumulation, both in the form of basidiocarp and in the mycelial form. Other species such as Agaricus subrufescens, Ganoderma lucidum, Lentinus crinitus, Pleurotus eryngii have also been evaluated. Bioaccumulated mycelial biomass with lithium can be considered a supplementation option for treatment against bipolar mood disorders, or as a prevention to suicide and even Alzheimer's, and further studies are needed.